Prevalence of non-communicable chronic diseases: arterial hypertension, diabetes mellitus, and associated risk factors in long-lived elderly people - Andreia Matos da Silva; Ariane Silva do Carmo; Vicente Paulo Alves; Luiz Sérgio Fernandes de Carvalho (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To identify the prevalence of non-communicable chronic diseases: arterial hypertension, diabetes mellitus, and associated risk factors in long-lived elderly people from three Brazilian regions. Methods: This is a multicenter, cross-sectional, and comparative study conducted with elderly people aged 80 years or older. Results: Higher prevalence of arterial hypertension were observed among those who use polypharmacy (75.7%), among elderly people aged between 80 and 84 years (33.9%), as well as in elderly people who are overweight (78.2%). The prevalence of diabetes was 24% (RP: 0.76; 95% CI: 0.59-0.98) lower among women compared to men and 2.15 times higher among those who use five or more medications (RP: 2.15; 95% CI: 1.63-2.85). Conclusions: In our sample, polypharmacy, body weight, and gender determine the prevalence of non-communicable chronic diseases: arterial hypertension and diabetes mellitus in long-lived elderly people.